Indigenous and minor vegetables of Manipur - Chanu, T M; Phurailatpam, A K; Singh, Barun; Singh, S R (Indian Horticulture, 2020)
The indigenous minor vegetables are available freely or consumed in many forms as raw or cooked by the Meitei community in Manipur from time immemorial. They are used for various local delicacies preparation due to its medicinal value and good taste. However, little attention has been paid on these crops and hence no proper scientific methods of nutritional and chemical profiling and agro techniques of these plants have not been worked out till now. Therefore, without further delay documentation should be done and conserved as a nutritional vegetable for the future generation.